Political, economic and social characteristics of political parties’ programmes in Serbia until 1918 - Kočović, Dragoslav R. (Sociološki pregled, 2019)
In this paper, we merely begin to discuss the establishment of political ideas, beginnings of political thought and political streams at the end of the first half of the 19th century, as the basis upon which political parties were formed several decades later. It was the time of great social turmoil and uncertain future of the young Serbian state. Serbia was recognized in 1878 after the liberation from the Ottoman rule and subsequently joined the family of world countries. Its beginning as a state was accompanied by numerous difficulties in establishing power, organizing political life and solving various social problems. The key part of this paper is dedicated to political parties, their formation and content turned into political programmes. We shall not delve into the political infrastructure nor study their exercise of power in the society. Our interests are directed at the political, economic and social content of political parties’ programmes in Serbia until 1918. We intend to highlight the value basis of Serbian community’s development and programme objectives used by the parties in their public communication. Taking into account that today Serbia is facing numerous challenges of political, economic, social and security nature, it is worth remembering the time 137 years ago in Serbia when its social life was formed. We can make a parallel between similarities and differences as well as challenges of this time and the past, from the perspective of one-century distance.
Keywords: party; programme; liberal; socialist; national; radical; democratic